Ridwan Kamil: the Result of Media Power in West Java - Dadan Kurnia; Arlan Siddha (Universitas Sultan Ageng Tirtayasa, 2022)
This research discusses the communication patterns of political actors experiencing development over time. After reform and experiencing information openness, Indonesia experienced the rapid development of information technology. The new media are widely used by various parties as a means of communication, not least by political actors to conduct political communication. This communication is concerned with the context of communication that is carried out to a large number of people through the mass media. This study will explain Ridwan Kamil's communication patterns as a political actor and regional head. The communication studied is communication conducted through Ridwan Kamil's personal Instagram page. This research uses qualitative methods, and the data collection techniques used are with primary and secondary data sources. In addition, researchers use theories by Rogers in Anis Hamidati to identify three basic traits that characterize the presence of new current media communication technologies, namely interactivity, de-massification, and asynchronous uses to support this research, such as political communication theory and current media theory.